(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article analyzes Venezuelan refugees’ communication and citizenship experiences in shelters of Operação Acolhida on the Brazil-Venezuela border. Based on the theoretical framework of communication, citizenship and migrations, we reflect on the agency of Venezuelan refugees to bypass the limitations of access to communication resources in the context of the tensions between control and mobility of migrants in border areas. The methodology includes observation and interviews with refugees and professionals that work in those shelters. The results indicate the relevance of the debate on communication as a right of migrants in relation to the access and distribution of communication resources.